1985
DOI: 10.1177/154079698501000103
|View full text |Cite
|
Sign up to set email alerts
|

Using a Behavior Chain Interruption Strategy to Teach Communication Skills to Students with Severe Disabilities

Abstract: Article Descriptors communication instruction; pictorial communication;behavior chain interruption; motivation; research; students with severe disabilities Two adolescents with severe disabilities were taught pictorial communication skills using an interrupted behavior sequence strategy. The independent variable involved insertion of a typical operant instructional trial for teaching communication skills into the midst of ongoing predictable sequences of behaviors, such as making toast or washing dishes, rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 9 publications
4
71
0
Order By: Relevance
“…For this behavior chain, a missing item format was used to contrive the MO for the needed item (i.e., coffee cup) and teach the new mand Bcup,^which ultimately lead to accessing the desirable item (i.e., coffee). This procedure was soon replicated in several follow-up studies (e.g., Alwell et al 1989;Goetz et al 1985;Hunt and Goetz 1988;Hunt et al 1986;Sigafoos et al 1989). These studies suggested that BCIS were a promising approach for teaching mands to children with developmental disabilities.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…For this behavior chain, a missing item format was used to contrive the MO for the needed item (i.e., coffee cup) and teach the new mand Bcup,^which ultimately lead to accessing the desirable item (i.e., coffee). This procedure was soon replicated in several follow-up studies (e.g., Alwell et al 1989;Goetz et al 1985;Hunt and Goetz 1988;Hunt et al 1986;Sigafoos et al 1989). These studies suggested that BCIS were a promising approach for teaching mands to children with developmental disabilities.…”
mentioning
confidence: 86%
“…First, some individuals might find an interruption aversive, which might provoke problematic mand forms, such as tantrums, aggression, or self-injury. To prevent this, it would seem useful to select interruption points that create an MO for manding but which are not overly aversive as described by Goetz et al (1985). Additionally, when using a BCIS that may signal a worsening condition, the listener might become a signal that reinforcement is not available, which could prevent the individual from emitting the targeted mand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unreasonable to expect the mere provision of an aided device will enable the learner to communicate. There is a growing literature describing effective procedures for teaching a variety of augmentative communication skills to learners with severe disabilities (Alwelt, Hunt, Goetz, & Sailor, 1989;Glennen & Calculator, 1985;Goetz, Gee, & Sailor, 1985;Hall & Sundberg, 1987;Reichle & Brown, 1985;Reichle et al, 1991;Romski et al, 1988). Despite this growing literature, data-based procedures for teaching some of the more specialized skills involved in using certain augmentative devices (e.g., eye gaze, linear, row/column, or directed scanning) are limited (Blackstone, 1989;Ratcliff, 1988).…”
Section: Availability Of Effective Teaching Proceduresmentioning
confidence: 95%
“…Goetz, Gee, and Sailor (1985) examined the use of a reinforcer specificity condition when the opportunity to mand was provided immedi ately after the learners' consumption or participation in the reinforcer had been interrupted. Their results sug gest that manding the continuation of an in-progress activity is an alternative to providing the S D prior to any immediate experience in the activity.…”
Section: Using Specific Reinforcers During Interventionmentioning
confidence: 99%